TANTANGAN MEMBENTUK KELUARGA SAKINAH PADA GENERASI MILENIAL - Zainal Arifin (STAI Syubbanul Wathon Magelang, 2020)
Islam asserts, fostering the ideal household (ma'ruf) is very important. A good household begins with loving (mawaddah), framed with a strong covenant bond (ghalidzan), and determines its ultimate goal, sakinah. The sakinah family is the finality and the crown of the household. Various efforts are made, strived to fulfill that. Predicate sakinah family there are at least elements of harmony, religious obedience, the length of marriage, honor, and have quality human resources. The Qur'an emphasizes the unity and continuity of the family. Even broken bonds (disintegrating) are recommended to be rebuilt again when goodness is possible. Sakinah is a family in the millenial era, not just religious ones. The ability to compete in the economic sphere, education also determines its existence. It is also important that the sakinah family pass on a generation of skilled, have character, have character and have global competitiveness.Family formation is very important. The previous modern era has left the problem of career women unsolved in the household environment. Many cases of divorce are caused by career problems of housewives. The researcher explained with qualitative methods based on theoretical and qualitative studies based on the field by processing data from deductive to inductive which the researchers collected through interviews with informants both in the religious court and outside the court which became the basis for data collection. the Sakinah family inherits a generation that is skilled (adept), has good character, has character and is competitive